Financial Constraints, Tax Burdens, and Firm Growth: Evidence from Indonesia - Arie, Ridhollah Muhammad (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2021)
Using a subjective measure of the constraints and data from World Bank Enterprise Survey, this paper investigates whether two business constraints, financial constraints and tax burdens, have the same impact on Indonesian firm growth. This paper employs instrumental variable estimation to handle endogeneity problems and finds that among the two business constraints examined in the analyses, only the financial constraint is a binding constraint that has a significantly negative impact on Indonesian firm growth, while taxes have a positive and significant impact on firm growth. Based on size classification, a significant impact is only found on large firms. Financial constraints and tax burdens are likely not to be binding constraints to firm growth for small firms, and the benefits from taxes are also not found on these firms. Further investigation of financial constraints reveals that private firms, manufacturing firms, and young firms are more sensitive to the negative impact of financial constraints.